Regulation, innovation and technology diffusion: Evidence from building energy efficiency standards in Germany - Makram El-Shagi; Claus Michelsen; Sebastian Rosenschon (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
The impact of environmental regulation on technology diffusion and innovations is studied using a unique data set of German residential buildings. We analyze how energy efficiency regulations, in terms of minimum standards, affects energy-use in newly constructed buildings and how it induces innovation in the residential-building industry. The data used consists of a large sample of German apartment houses built between 1950 and 2005. Based on this information, we determine their real energy requirements from energy performance certificates and energy billing information. We develop a new measure for regulation intensity and apply a panel-error-correction regression model to energy requirements of low and high quality housing. Our findings suggest that regulation significantly impacts technology adoption in low quality housing. This, in turn, induces improvements in the high quality segment where innovators respond to market signals.
Keywords: D2; Q4; R5; 330; environmental regulation; innovation; technology diffusion; residential real estate; energy efficiency